2012
DOI: 10.1007/s00261-011-9839-1
|View full text |Cite
|
Sign up to set email alerts
|

Response to neoadjuvant therapy in locally advanced rectal cancer: assessment with diffusion-weighted MR imaging and 18FDG PET/CT

Abstract: The aim of this study was to evaluate the correlation between the changes of SUV(max) and of apparent diffusion coefficient (ADC) before and after neoadjuvant therapy, to enable us predict the therapy response, in patients with locally advanced rectal cancer (LARC). A total of 30 patients with LARC who underwent CRT were recruited for our study. All the patients underwent a whole body 18F-FDG-PET/CT scan and a pelvic MR examination including DW imaging for staging (PET/CT1 and RM1), and after the chemoradiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 17 publications
3
42
1
Order By: Relevance
“…The main challenge for posttreatment assessment lies in differentiating between viable lymphomatous lesions and fibrotic tissue. Several previous studies in different malignancies have reported ADC measurements to be useful in the differentiation between residual or recurrent tumor and posttreatment changes . All these studies show an increase in sensitivity and specificity when adding (quantitative) DWI to the routine MRI sequences with significantly lower ADCs in residual or recurrent malignant lesions compared with those in (immature) fibrosis and granulation tissue, in keeping with the results of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…The main challenge for posttreatment assessment lies in differentiating between viable lymphomatous lesions and fibrotic tissue. Several previous studies in different malignancies have reported ADC measurements to be useful in the differentiation between residual or recurrent tumor and posttreatment changes . All these studies show an increase in sensitivity and specificity when adding (quantitative) DWI to the routine MRI sequences with significantly lower ADCs in residual or recurrent malignant lesions compared with those in (immature) fibrosis and granulation tissue, in keeping with the results of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…These findings suggest that baseline DWI may not have a prognostic value and may not predict response to treatment. This was reported also in patients with rectal cancer: pretherapy ADC values of responders were not significantly different from those of nonresponders (29,30). In contrast, it has been reported that early changes in ADC values can indicate the difference in response to treatment, as tumors with greater ADC increase tend to demonstrate a better response (22).…”
Section: Discussionmentioning
confidence: 76%
“…Ippolito et al [71], in a series of 30 patients with LARC who underwent CRT, showed a significantly higher mean value of SUV max in PET/CT before treatment than after treatment along with a significantly lower ADC value before treatment than after treatment. The best predictors cut-off values for response were SUV max of 4.4 and an ADC value of 1.289 × 10 −3 mm 2 /s with sensitivity, specificity, accuracy, negative predictive value, and positive predictive values of 77.3%, 88.9%, 80.7%, 61.5%, and 94.4%, respectively.…”
Section: Future Trends and Conclusionmentioning
confidence: 97%